SELF-ACCEPTANCE AMONG THE ELDERLY IN THE TRESNA WERDHA CENTER IN BENGKULU - Made Cintia Rupawani; Ishak Fadlurrohim; Indria Agustina (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
This study aims to gain a deeper and more comprehensive understanding of self-acceptance among elderly individuals living at Panti Sosial Tresna Werdha Bengkulu, focusing on the factors that influence this psychological condition. Using a descriptive qualitative method, the research involved five elderly participants who served as key informants and provided detailed explanations regarding their personal experiences, perceptions, and reflections about life in the institution. The findings show that seven out of ten identified factors contribute positively to self-acceptance. These factors include the ability to understand oneself, having realistic expectations, the absence of significant environmental barriers, the lack of severe emotional disturbances, past achievements that strengthen confidence, maintaining a stable self-concept, and experiencing positive parenting earlier in life. These positive influences are supported by healthy thinking patterns, relatively good physical conditions, and emotional resilience in managing current challenges. However, three factors were found to hinder self-acceptance: receiving positive attitudes from others, identifying with well-adjusted individuals, and having a broad self-perspective. These inhibiting factors are associated with disharmonious peer relationships and a tendency for individuals to rely primarily on personal judgment rather than external input. In conclusion, the study highlights that self-acceptance among the elderly is shaped by both internal and external factors. It is recommended that elderly care institutions strengthen social and emotional support, and that further research be conducted to explore these influences more deeply in order to develop effective interventions that improve the well-being and overall quality of life of older adults. Key words: self-acceptance, elderly, social institution